Comparison of fast switching high current power devices - Shelton, E; Ali, K; Han, R; Rogers, D; Carter, J; Louco, L; Beadman, M; Palmer, P (VDE, 2021)
New GaN and SiC wide bandgap power devices offer impressively fast switching performance compared to their traditional Silicon counterparts. However, Silicon devices have not stood still, and new generations of these devices offer excellent performance at competitive prices. This paper makes a comparative study between the latest generation of high-current SiC, GaN, Si CoolMOS and Si IGBT power switching devices, switched as fast as possible using low inductance circuit design and no external gate resistors. An analysis of the factors that determine switch edge-rate is presented, along with an overview of circuits developed by the authors to achieve accurate measurement of switching energy loss.